Utilization of Seismic Data as a Tsunami Vulnerability Review - Khusnani, Azmi; Jufriansah, Adi; Afriyanto, Mulya (Indonesian Review of Physics, 2022)
This study aimed to analyze seismic data, which is then made into an infographic to map the level of tsunami hazard in the Sikka District. The research was carried out in Sikka District, East Nusa Tenggara, located between 121°55'40''-122°41'30'' east longitude and 08°22'-08°50' south latitude. The data source comes from the IRIS Earthquake Browser, and the analysis stage was carried out in two phases. The first analysis used seismic data analysis, and EQ Energy used IRIS (Incorporated Research Institutions for Seismology) data. Meanwhile, the second analysis maps the tsunami risk by determining the tsunami hazard in areas with the potential for a tsunami. Based on the analysis of seismicity data showed that Sikka District has the potential for an earthquake accompanied by a tsunami. In contrast, the results of the EQ Energy analysis caused by the December 14, 2021 earthquake were known as the value of Ehf = 6.46 × 1014 J  and EBB = 5.48 × 1015 J. The analysis of the level of tsunami susceptibility based on the tsunami run-up height in Sikka District showed that the northern coastal area of ​​Flores had various potentials, where the highest vulnerability level was in the Alok subdistrict and parts of Talibura. Meanwhile, the area with the lowest potential was the Kewapante subdistrict.